Kadar Gula Darah, Tekanan Darah dan Mortalitas Pasien dengan Cerebrovascular Accidents Berulang - Laksono, Bayu Budi (FORIKES, 2024)
Cerebro vascular accident or stroke is an emergency neurological disease that is acute and requires immediate treatment. Mechanical, nervous and humoral factors contribute to changes in the composition and structure of the cerebrovascular wall. It is estimated that 30% of patients with cerebral atherosclerosis suffer from diabetes mellitus. Patients with this condition have twice the potential to suffer a second attack of cerebro vascular accident compared to patients without diabetes mellitus. This study aimed to analyze the relationship between blood sugar levels and blood pressure and mortality in patients with recurrent cerebro vascular accidents. This study used a cross-sectional design. The respondents of this study were all recurrent cerebro vascular accident patients from January to October 2017 at the Stroke Unit of Dr. Hospital. Soepraoen Malang numbered 48 people, selected using total sampling technique. The examination result data was analyzed using a correlation test, namely the contingency coefficient. The results of the analysis showed that the p value for the correlation analysis between blood glucose levels and mortality in cerebro vascular accident patients was 0.509. To test the correlation between blood pressure and mortality, the p value = 0.049. It was concluded that cerebro vascular accident mortality in the Stroke Unit of Dr. Hospital. Soepraoen Malang is related to the patient's blood pressure.Keywords: cerebro vascular accident; mortality; blood pressure ABSTRAK Cerebro vascullar accident atau stroke merupakan penyakit neurologi gawat darurat yang bersifat akut dan membutuhkan penanganan segera. Faktor mekanik, saraf dan humoral berkontribusi terhadap perubahan komposisi dan struktur dinding serebrovaskular. Diperkirakan 30% pasien dengan aterosklerosis otak menderita diabetes mellitus. Pasien dengan kondisi tersebut memiliki potensi dua kali lebih besar terkena cerebro vascullar accident serangan kedua dibandingkan dengan pasien non diabetes mellitus. Penelitian ini bertujuan untuk menganalisis hubungan antara kadar gula darah dan tekanan darah dengan mortalitas pasien dengan cerebro vascullar accident berulang. Penelitian ini menggunakan desain cross-sectional. Responden penelitian ini adalah semua pasien cerebro vascullar accident berulang pada bulan Januari sampai dengan oktober 2017 di Unit Stroke Rumah Sakit Dr. Soepraoen Malang sejumlah 48 orang, yang dipilih dengan teknik total sampling. Data hasil pemeriksaan dianalisis menggunakan uji korelasi yakni koefisien kontigensi. Hasil analisis menunjukkan bahwa nilai p untuk analisis korelasi antara kadar glukosa darah dengan mortalitas pasien cerebro vascullar accident adalah 0,509. Untuk uji korelasi antara tekanan darah dan mortalitas didapatkan nilai p = 0,049. Disimpulkan bahwa mortalitas cerebro vascullar accident di Unit Stroke Rumah Sakit Dr. Soepraoen Malang berhubungan dengan tekanan darah pasien.Kata kunci: cerebro vascullar accident; mortalitas; tekanan darah